Past, current, and potential future distributions of unique genetic diversity in a cold‐adapted mountain butterfly. Issue 20 (30th September 2020) - Minter, Melissa; Dasmahapatra, Kanchon K.; Thomas, Chris D.; Morecroft, Mike D.; Tonhasca, Athayde; Schmitt, Thomas; Siozios, Stefanos; Hill, Jane K.
Abstract: Aim: Climatic changes throughout the Pleistocene have strongly modified species distributions. We examine how these range shifts have affected the genetic diversity of a montane butterfly species and whether the genetic diversity in the extant populations is threatened by future climate change. Location: Europe. Taxon: Erebia epiphron Lepidoptera: Nymphalidae. Methods: We analyzed mtDNA to map current genetic diversity and differentiation of E. epiphron across Europe to identify population refugia and postglacial range shifts. We used species distribution modeling (SDM) to hindcast distributions over the last 21, 000 years to identify source locations of extant populations and to project distributions into the future (2070) to predict potential losses in genetic diversity. Results: We found substantial genetic diversity unique to specific regions within Europe (total number of haplotypes = 31, number of unique haplotypes = 27, H d  = 0.9). Genetic data and SDM hindcasting suggest long‐term separation and survival of discrete populations. Particularly, high rates of unique diversity in postglacially colonized sites in England ( H d  = 0.64) suggest this population was colonized from a now extinct cryptic refugium. Under future climate change, SDMs predict loss of climate suitability for E. epiphron, particularly at lower elevations (<1, 000 meters above sea level) equating to 1 to 12 unique haplotypes being at risk under climate scenarios projecting 1°C and 2–3°C increases respectfully in global temperature by 2070. Main conclusions: Our results suggest that historical range expansion and retraction processes by a cold‐adapted mountain species caused diversification between populations, resulting in unique genetic diversity which may be at risk if distributions of cold‐adapted species shrink in future. Assisted colonizations of individuals from at‐risk populations into climatically suitable unoccupied habitat might help conserve unique genetic diversity, and translocations into remaining populations might increase their genetic diversity and hence their ability to adapt to future climate change. Abstract : The genetic diversification of cold‐adapted mountain species, such as E. epiphron, has been shaped by Pleistocene glaciations, resulting in unique genetic diversity in isolated populations. The unique genetic diversity in mountain and cold‐adapted species is at under future climate warming, and we predict E. epiphron will lose 38%–64% of its range in the future, resulting in the loss of genetic diversity, reducing its ability to adapt.